Efek Aplikasi Patch Gingiva Mukoadesif β-Carotene Akibat Paparan Radiografi Panoramik - Rurie Ratna Shantiningsih; Silviana Farrah Diba (Majalah Kedokteran Gigi Indonesia, 2015)
Effect of β-carotene Gingival Mucoadhesive Patch Application at Panoramic Radiography Exposure. According to previous research, β-carotene gingival mucoadhesive patch has a radiation protection effect on New Zealand Rabbits. The increase in micronucleus after panoramic radiography exposure is avoided because of β-carotene gingival mucoadhesive patch application. In order to continue that research, we try the application of β-carotene gingival mucoadhesive patch into human. Twenty subjects who requested to take panoramic radiography were divided into two groups randomly. Group I was without β-carotene gingival mucoadhesive patch application and Group II was given the application before radiography exposure. Each of the subjects was swabbed on anterior maxillary gingiva before radiography exposure and the 10th day after the exposure. The swab was stained using modified Feulgen Rossenbeck method. The adhesive time and the effect of radiograph were also observed. The result shows that there was a decrease in micronucleus number after β-carotene gingival mucoadhesive patch application but there was no significant difference (p>0,05) between Grup I and II. The adhesive time was more than 10 hours and there was uncomfortable taste in the first time application. Gray scale analysis shows no significant difference (P>0,05) between panoramic radiography application and without application. The conclusion is that β-carotene gingival mucoadhesive patch application reduces micronucleus number although not significantly.